A Survey of Mesenchyme-related Tumors of the Rat Kidney in the National Toxicology Program Archives, with Particular Reference to Renal Mesenchymal Tumor. (August 2016) - Hard, Gordon C.; Seely, John Curtis; Betz, Laura J.
In order to harmonize diagnostic terminology, confirm diagnostic criteria, and describe aspects of tumor biology characteristic of different tumor types, a total of 165 cases of mesenchyme-related tumors and nephroblastomas of the rat kidney were reexamined from the National Toxicology Program (NTP) Archives. This survey demonstrated that renal mesenchymal tumor (RMT) was the most common spontaneous nonepithelial tumor in the rat kidney, also occurring more frequently in the NTP studies than nephroblastoma. Renal sarcoma was a distinct but very rare tumor entity, representing a malignant, monomorphous population of densely crowded, fibroblast-like cells, in which, unlike RMT, preexisting tubules did not persist. Nephroblastoma was characterized by early death of affected animals, suggesting an embryonal origin for this tumor type. Male and female rats were equally disposed to developing RMT, but most of the cases of nephroblastoma occurred in female rats and liposarcoma occurred mostly in male rats. This survey confirmed discrete histopathological and biological differences between the mesenchyme-related renal tumor types and between RMT and nephroblastoma. Statistical analysis also demonstrated a lack of any relationship of these renal tumor types to test article administration in the NTP data bank.